Some causes of structural changes in the economy (the case of economy of Kazakhstan) (International relations and international law Journal, 2018)
The transition of society development in the post-industrial phase requires a fundamental change in the structure of the national economy. Here, especially should pay attention to the increase in the share ofdownstream of industry and services in the structure of national economy, as well as ongoing support them. There are some historical, political, legal, socio-economic and institutional preconditions, which act as reasons for the implementation of structural changes in the economy. This article analyzes some of these causes, including change of ownership, the influence of the international division of labour on the structure of the economy, changes in the global economy, crisis, etc. Indue to these causes need rationale of structural change in the economy of Kazakhstan.Key words: structural changes, innovative development, economic growth, post-industrial development.